Analysis Mapping Area Prone Criminal In Subdistrict Mojolaban Using the Choropleth Maps Method - ardita widya putri, ardita widya putri; Rohsulina, Pranichayudha (Universitas Veteran Bangun Nusantara, 2024)
Crime is a detrimental act that often occurs in society because it has many negative impacts on society. Reporting from Jatimnetwork.com, Mojolaban District is the 4th busiest sub-district in Sukoharjo Regency, where the number of people living in Mojolaban District in 2022 will reach 97,459 people, where achieving a decent life is very high. This thing becomes Big homework for the government and Mojolaban Police to be able to handle and make efforts to overcome crime in Sukoharjo, especially in Mojolaban District. This research used the choropleth maps method with Descriptive Observation and mapped crime-prone areas using ArcGIS. There are several types of crime cases that occur in Mojolaban District, such as embezzlement, theft, sexual harassment, assault, fraud, beatings, fraud and embezzlement. Of these cases, the one with the highest number is case thief And theft Which often happen is theft box infaq, motor And car.